COPING MECHANISMS AND DEPRESSION IN ADOLESCENTS WITH DRUG ABUSE - Yufi Aris Lestari; Hartin Suidah; Ninik Murtiyani; Riska Aprilia Wardani (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2021)
Introduction: The high level of depression or life problems among adolescents impacted different coping for each individual intending to overcome the problems that occur. This study aimed to determine the relationship between levels of depression and coping mechanisms of adolescent drug users.Methods: This study was a correlational analytic research with cross-sectional approach. The sampling technique was simple random sampling. This study's sample was 32 adolescent drug users undergoing rehabilitation at the drug rehabilitation facility Rumah Obit Surabaya. Depression variables was measured used the Beck Depression Inventory questionnaire, and variable coping mechanisms used the Ways of Coping Checklist questionnaire. The data was analyzed using the rho spearmen test.Results: The analysis result showed that coping mechanism had a significant relationship with depression in adolescent drug users with p-value = 0.001 (p <0.05). The adolescent drug users mostly experienced mild depression as many as 25 respondents (78.1) and maladaptive coping mechanism as many as 21 (65.6%).Conclusion: Optimizing socialization to increase knowledge about the impact of drug use on adolescents is needed to prevent depression in adolescent therefore they can use adaptive coping mechanisms in problem solving.